2021
DOI: 10.3389/fneur.2021.738272
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ADGRV1 Gene in Familial Forms of Genetic Generalized Epilepsy

Abstract: Background: Genetic generalized epilepsies (GGE) including childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), juvenile myoclonic epilepsy (JME), and GGE with tonic–clonic seizures alone (GGE-TCS), are common types of epilepsy mostly determined by a polygenic mode of inheritance. Recent studies showed that susceptibility genes for GGE are numerous, and their variants rare, challenging their identification. In this study, we aimed to assess GGE genetic etiology in a Sudanese population.Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In addition, it has been found that different mutations in mouse models for Vlgr1/Adgrv1 are associated with audiogenic epilepsy 3 . However, over the last years, there is also growing evidence that mutations in VLGR1/ADGRV1 also can cause different forms of epilepsy in humans 10,11 . Concrete knowledge of VLGR1's molecular function and signalling is necessary for gaining insights into the pathomechanisms and the elucidation of potential targets for therapies of diseases related to VLGR1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been found that different mutations in mouse models for Vlgr1/Adgrv1 are associated with audiogenic epilepsy 3 . However, over the last years, there is also growing evidence that mutations in VLGR1/ADGRV1 also can cause different forms of epilepsy in humans 10,11 . Concrete knowledge of VLGR1's molecular function and signalling is necessary for gaining insights into the pathomechanisms and the elucidation of potential targets for therapies of diseases related to VLGR1.…”
Section: Introductionmentioning
confidence: 99%
“…Besides USH2C, defects, namely haploinsufficiency of VLGR1/ADGRV1 can also lead to the development of epilepsy in humans 9,56 and audiogenic epilepsy in mice 2 . There is increasing evidence that alterations in autophagy are present in epileptogenesis, leading to imbalanced excitatory-inhibitory neurotransmission and epilepsy-induced neuronal damage 57,58 .…”
Section: Multiple Signals Downstream Of Gpcrs Regulate Autophagymentioning
confidence: 99%
“…Mutations in the VLGR1/ADGRV1 gene cause Usher syndrome type 2C (USH2C) which is characterized by congenital sensorineural hearing loss and retinitis pigmentosa (RP) 7 . Additionally, mutations, even haploinsufficiency of VLGR1/ADGRV1 have been associated with different forms of epilepsy in humans and audiogenic seizures in mice (Dahawi et al 2021;Myers et al 2018; Zhou et al 2022). Almost nothing is known to date about the pathomechanisms underlying epileptogenesis that lead to the imbalance between excitatory and inhibitory neurotransmission described in epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been found that different mutations in mouse models for Vlgr1/Adgrv1 are associated with audiogenic epilepsy 9 . However, over the last years there is also growing evidence that mutations in VLGR1/ADGRV1 also can cause different forms of epilepsy in humans 12,13 . Concrete knowledge on VLGR1´s molecular function and signaling is necessary for gaining insights into the pathomechanisms and the elucidation of potential targets for therapies of diseases related to VLGR1.…”
Section: Introductionmentioning
confidence: 99%